Structural and functional studies of STAT1 from Atlantic salmon (Salmo salar) - Skjesol, Astrid (BioMed Central, 2010)
BACKGROUND: Type I and type II interferons (IFNs) exert their effects mainly through the JAK/STAT pathway, which is presently best described in mammals. STAT1 is involved in signaling pathways induced by both types of IFNs. It has a domain-like structure including an amino-terminus that stabilizes interaction between STAT dimers in a promoter-binding situation, a coiled coil domain facilitating interactions to other proteins, a central DNA-binding domain, a SH2 domain responsible for dimerization of phosphorylated STATs and conserved phosphorylation sites within the carboxy terminus. The latter is also the transcriptional activation domain. RESULTS: A salmon (Salmo salar) STAT1 homologue, named ssSTAT1a, has been identified and was shown to be ubiquitously expressed in various cells and tissues. The ssSTAT1a had a domain-like structure with functional motifs that are similar to higher vertebrates. Endogenous STAT1 was shown to be phosphorylated at tyrosine residues both in salmon leukocytes and in TO cells treated with recombinant type I and type II IFNs. Also ectopically expressed ssSTAT1 was phosphorylated in salmon cells upon in vitro stimulation by the IFNs, confirming that the cloned gene was recognized by upstream tyrosine kinases. Treatment with IFNs led to nuclear translocation of STAT1 within one hour. The ability of salmon STAT1 to dimerize was also shown. CONCLUSIONS: The structural and functional properties of salmon STAT1 resemble the properties of mammalian STAT1.